Stimulation of the Internal Ribosome Entry Site (IRES)-Dependent Translation of Enterovirus 71 by DDX3X RNA Helicase and Viral 2A and 3C Proteases - Su, Yu-Siang; Tsai, Ai-Hsuan; Ho, Yueh-Feng; Huang, Shin-Yi; Liu, Yen-Chun; Hwang, Lih-Hwa (Frontiers in Microbiology, 2018)
The translation of enterovirus 71 (EV71) is mediated by an internal ribosome entry site (IRES)-dependent manner. EV71 IRES comprises five highly structured domains (domains II-VI) in the 5’-untranslated region of the viral mRNA. A conserved AUG triplet residing in domain VI is proposed to be the ribosome entry site. It is thus envisaged that the highly structured conformation of domain VI may actually reduce the accessibility of the AUG triplet to the ribosome. This study identified a DEAD-box family RNA helicase, DDX3X, that positively regulated the EV71 IRES-dependent translation. The helicase activity of DDX3X was required for the stimulation of EV71 IRES activity; however, DDX3X was no longer important for the IRES activity when the secondary structure of domain VI was destabilized. DDX3X interacted with the truncated eIF4G which bound specifically to domain V. Thus, we proposed that DDX3X might bind to domain VI or a region nearby via the interaction with the truncated eIF4G, and subsequently unwound the secondary structure of domain VI to facilitate ribosome entry. Additionally, we demonstrated that the viral 2Apro and 3Cpro enhanced the IRES-dependent translation via their protease activities. Together, these results indicate that DDX3X is an important RNA helicase involved in EV71 IRES-dependent translation and that IRES translation is enhanced by viral infection, partly mediated by viral protease activity.